Are Children's Socio-Emotional Skills Shaped by Parental Health Shocks? - Esteban García-Miralles; Miriam Gensowski (Center for Economic Studies and ifo Institute (CESifo), 2022)
Child skills are shaped by parental investments. Health shocks to parents can affect these investments and their children's skills. This paper estimates causal effects of severe parental health shocks on child socio-emotional skills. Drawing on a large-scale survey linked to hospital records, we find that socio-emotional skills of 11-16 year-olds are robust to these shocks, except for small reductions in Conscientiousness. We estimate short-run effects with child-fixed effects and dynamics around shocks with event studies. In the long-run, we find some evidence of build-up of effects that may be rationalized with shocks having a delayed impact on children's skills.
Keywords: J24; I10; I21; 330; Big Five personality traits; development of personality traits; parental health shocks; socio-emotional skills; non-cognitive skills; skill formation